Analisis Penggunaan Media Sosial dalam Proses Pembelajaran di Era Digital pada Mahasiswa Teknologi Pendidikan FIP UNP - Azkia, Anami Azkal; Zelhendri Zen; Yeni J, Fetri; Anugrah, Septriyan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Social media is not only a platform for social interaction, but it has also been widely used in educational contexts. The use of social media has both positive and negative sides. This research aims to analyze the use of social media in the learning process in the digital era on students of Educational Technology FIP UNP. This research was designed using qualitative research with descriptive methods. Data were obtained from students of Educational Technology FIP UNP. The data collection techniques used were observation, interviews and documentation. Data analysis techniques using Milles and Huberman techniques, namely data reduction, data presentation and continued with conclusion drawing. While testing the validity of the data is done by triangulation, peer checking, using reference materials and conducting audits with the supervisor. The results showed that social media that are often used by students of Educational Technology FIP UNP in the learning process in the digital era are Whatsapp, Instagram, Telegram, Youtube, TikTok and Zoom. The application is often used because of the convenience of the features offered and is familiar with most people. The way social media is used in the learning process is different, adjusting to the lecturer and the course.